Berth allocation with service limitations on vessels. Issue 2 (2nd April 2016) - Li, Ming-Kun
ABSTRACT: This paper considers a vessel berth allocation problem in a river terminal with service limitations due to different water depths along the terminal. It aims at reducing the total service time for all vessels and barges, while the quay is divided into vessel berth sections and barge berth sections for berthing ships of different drafts. An integer programming model is proposed, and properties of this formulation are analysed. Then, the structure of the formulation is used to propose a fix-and-optimise heuristic. Numerical simulations were conducted to test the performance of the solution approach. The results indicate that the proposed method is efficient and obtains good feasible solutions in many test instances. Further discussions explore the factors relating to berthing barges in the vessel berth sections of a river terminal that contribute to introducing a better ship-berthing strategy to this terminal according to its resources and conditions.